The experimental infection with a field isolate of the infectious bronchitis virus from eastern Saudi Arabia resulted in seroconversion of the challenged birds with no apparent clinical diseases - Hemida, Maged Gomaa (Virusdisease, 2021)
The infectious bronchitis virus (IBV) is still one of the major respiratory viral pathogens of chickens. The IBV infection resulted in a wide range of clinical syndromes in the affected chickens, including respiratory, renal, gonads affections as well as generalized infections. Despite the intensive application of various commercial vaccines against the virus, many outbreaks are still reported in chickens worldwide. Several studies reported the circulation of several strains and genotypes of the IBV in eastern Saudi Arabia. The main goal of the current study was to isolate some of the circulating strains of IBV and assess its ability to reproduce the IBV infections in the challenge birds. Another objective was to monitor the immune status of the infected chickens during the course of this study. To achieve these goals, we used some filed IBV isolates retrieved from an outbreak in a broiler chicken farm in eastern Saudi Arabia in 2014. A total of 220-day-old chickens (110 Ross and 110 native Saudi breed chickens), twenty birds per each group, were used in this study. The chickens in some groups received some IBV vaccines on day one of the experiment, and some are boosted on day 19. All birds were challenged on day 28 of the experiment. Our results showed mild IBV signs in the non-vaccinated control group of chickens; however, the vaccinated chickens did not show any signs of IBV infections. Meanwhile, both the vaccinated and the none- vaccinated birds seroconverted to the IBV as shown by the ELISA results. In conclusion, the response of the IBV infected birds is mainly driven by the vaccination plans they received as a prime-boost regime. Further studies are required for a better understanding of the dynamics of IBV infection in native Saudi chickens.